2014
DOI: 10.1002/acp.3055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of the Self‐Administered Interview© for Witnesses with Autism Spectrum Disorder

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 63 publications
4
37
0
1
Order By: Relevance
“…Therefore, the interpretation of the source memory results should be considered with caution and we strongly encourage future research to explore these issues further. Corroborating our findings, however, a recent study by Maras, Mulcahy, Memon, Picariello, and Bowler (2014) suggests that providing retrieval support with the SAI© may not be an appropriate strategy for witnesses with ASD. Specifically, the SAI© elicited less accurate reports from participants with ASD than a control interview that lacked retrieval support components.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, the interpretation of the source memory results should be considered with caution and we strongly encourage future research to explore these issues further. Corroborating our findings, however, a recent study by Maras, Mulcahy, Memon, Picariello, and Bowler (2014) suggests that providing retrieval support with the SAI© may not be an appropriate strategy for witnesses with ASD. Specifically, the SAI© elicited less accurate reports from participants with ASD than a control interview that lacked retrieval support components.…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, we highlight that these null results do not mean that these techniques should be rejected for children with ASD. We acknowledge that beneficial effects of these investigative interview adaptations may not be in relation to the parameters measured in our studyvolume and accuracy of recall (also see Bowler, 2010, andMaras, Mulcahy, Memon, Picariello, &Bowler, 2014, for data suggesting that alternative interview techniques may not improve recall in autistic adults). We further acknowledge that some of the interview adaptations investigated may actually be the critical factor in determining whether a child with ASD can give any evidence at all.…”
mentioning
confidence: 87%
“…It should be emphasised, again, that it is not unusual to find that interventions that appear to work well for TD children and adults may not have the same results in those with ASD (cf. Maras & Bowler, 2010;Maras et al, 2014). We finish by highlighting an important inaccuracy in Dando and colleagues' letter.…”
mentioning
confidence: 87%
“…It is suggested that discussing neutral topics can build rapport, creating a positive mood, trust, empathy, while reducing anxiety and unreliable information (Fisher & Geiselman, 1992;Milne & Bull, 1999;Shepherd, 1993). However, individuals with ASD can find establishing empathy to be difficult, due to the social impairments which characterise ASD, and taking part in 'small talk' can increase anxiety, rather than reduce it (Frith, 2008;Maras, Mulcahy, Memon, Picariello, & Bowler, 2014). Individuals with ASD can unintentionally act and respond in a manner that suggests a lack of respect or defiance, which can result in the interviewer adopting a negative bias of the suspect (Murrie, Warren, Kristiansson, & Dietz, 2002).…”
Section: Peace Interview Frameworkmentioning
confidence: 99%
“…Those with ASD can be unable to determine what information is relevant when reconstructing an experience or giving a narrative and may produce vague answers which are unhelpful to the investigation (Losh & Capps, 2003;White, Burgess, & Hill, 2009). Due to the impairment of social imagination in individuals with ASD, suspects may have difficulty remembering experiences in context, particularly in situations which are cognitively demanding or stressful (Maras et al, 2014). Research has suggested that this phase of the interview, similarly to the cognitive interview model, is unsuitable for individuals with ASD, and that information gained can be inaccurate (Maras & Bowler, 2010).…”
Section: Peace Interview Frameworkmentioning
confidence: 99%